Growth and production of indigenous Katokkon chilies of Toraja (Capsicum chinense jacq) in various organic Tithonia compost compositions. Issue 1 (October 2021) - Kaimuddin,; Ulfa, F; Stoeber, S; Ramba, T; Iswoyo, H; Dermawan, R; Sjam, S; Yassi, A; Fatmawati,
Abstract: This study aimed to investigate the effect of Tithonia compost application on the growth and production of several indigenous Katokkon chili (Capsicum chinense Jacq) of Toraja regency, South Sulawesi, which is based on the morphological appearance, that were assumed to be differently. The field experiment was conducted in the Village of Tallangsura, Buntao District, North Toraja Regency. The site is located at the altitude of 800 meters above sea level with a minimum temperature of 18.7°C - 20.1°C and a maximum temperature of 20.1°C - 29.4°C. The experiment was conducted as Split Plot Design consisting of 2 factors. The whole-plot factor consisted of three Katokkon chili landraces, i.e. Limbong Sampolo, Leatung #1 and Leatung #2. The split-plot factor was compost at 3 levels of Tithonia levels: 12.5%, 25.0%, and 37.5% of Tithonia, respectively. Each treatment was repeated 3 times and consisted of 15 plants in each plot. The results showed that the Leatung #2 Katokkon chili and 37.5% of Tithonia compost had the highest yield at 46 days after planting (DAP), and the best plant height of 38.78 cm. The Leatung #1 Katokkon chili and 25.0% of Tithonia compost produced the most productive branches at 60 DAP with 44.33 branches. With 7.62% the Limbong Sampolo Katokkon chili had the lowest percentage of fallen fruits, while the Leatung#2 Katokkon chili accession showed the highest fruit diameter with 3.35 cm.